Experimental techniques in optimization of the process of injection molding of thermoplastics - After-shrinkage of moldings - Bogucki, M.; Płaska, S.; Stączek, P. (Polimery, 2022)
Experimental presentation of the problem of injection molding of thermoplastics (low density PE) optimization, using injection molding machines of one pressure degree and constant injection rate. The two-level fractional factorial design and the method of steepest descent, being together a sequence procedure of experimental investigations, were used. The solution takes into consideration five investigated parameters (mold temperature, temperature of a polymer, injection time, time of moldings cooling, pressure Table 1) and one result parameter - after-shrinkage of moldings (s). Particular steps of optimization investigations were described, viz. survey measurements (Figs. 1 and 2), looking for extremum neighborhood (Tables 2-5) and determination of a model approximating s value at extremum neighborhood (Table 6, Fig. 4). Coordinates of the point of factorial space for minimal s value were determined (Table 7). It has been found that low temperature of injection mold, long time of moldings cooling and high value of pressure show the biggest effects on shrinkage decrease. The method described let make the optimization independent on injection molding machine construction as well as on character and number of optimization criteria.